2016
DOI: 10.4028/www.scientific.net/msf.838-839.512
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Modeling for the Simulation of the Superplastic Forming of AA5083

Abstract: The AA5083 alloy is already being used in applications that require lightweight construction and moderate strengths. In order to carry out accurate simulations of the superplastic forming of this alloy, the used constitutive models should be able to predict the deformation and thinning behavior during the forming process. In this paper, we compare the dome height and pole thickness evolution during gas bulge forming using different AA5083 constitutive material models. The models considered have different level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Accurate constitutive material models are essential for the realistic simulation of the SPF process. Many established models found in the literature are identified as phenomenological material models [6][7][8][9][10][16][17][18][19][20][21]. These are viscoplastic models that represent the macroscopic behavior of deformation, usually at a constant forming temperature.…”
Section: Constitutive Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate constitutive material models are essential for the realistic simulation of the SPF process. Many established models found in the literature are identified as phenomenological material models [6][7][8][9][10][16][17][18][19][20][21]. These are viscoplastic models that represent the macroscopic behavior of deformation, usually at a constant forming temperature.…”
Section: Constitutive Modelingmentioning
confidence: 99%
“…They reflect mainly the relationship between the effective flow stress and the effective strain and strain rate. The constants in these models are fitted using uniaxial tensile [10] or bulge forming experimental data [9,20,21].…”
Section: Constitutive Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Low level of flow stress and high strain rate sensitivity of the material are the main features of superplastic deformation. In order to describe material behavior during superplastic deformation, the Backofen constitutive equation [ 2 ], using power relation between flow stress and strain rate , is commonly used [ 3 , 4 ] where and are the material constants. The strain rate sensitivity index is an important parameter responsible for the stability of plastic flow.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients of Equation (1) are calculated by the approximation of the measured flow stress values for different strain rates. However, in some investigations [ 3 , 6 , 7 , 8 , 9 ] it was shown that free bulging testing is a more suitable experimental technique for characterization of a material formed in biaxial tension conditions. The comparison of material characteristics obtained by free bulging and tensile tests for aluminum based alloys is presented in [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%